2009
DOI: 10.1007/s10552-009-9423-y
|View full text |Cite
|
Sign up to set email alerts
|

Marine n-3 polyunsaturated fatty acids in adipose tissue and breast cancer risk: a case–cohort study from Denmark

Abstract: This study does not indicate any association between the content of total or individual marine n-3 PUFA in adipose tissue and development of BC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 38 publications
1
23
0
1
Order By: Relevance
“…The results obtained by administering DHA to the cells were confirmed in mice fed with fish oil [116]. In several epidemiological studies, it has been shown that a deficiency in omega-3 FAs increases the probability to develop metastases, while a diet rich in omega-3 FAs can reduce their size [117][118][119]. According to these results, women affected by metastatic breast cancer supplemented with 1.8 g of DHA during chemotherapy with antracyclins could increase their survival by 8 months.…”
Section: Breast Cancermentioning
confidence: 72%
“…The results obtained by administering DHA to the cells were confirmed in mice fed with fish oil [116]. In several epidemiological studies, it has been shown that a deficiency in omega-3 FAs increases the probability to develop metastases, while a diet rich in omega-3 FAs can reduce their size [117][118][119]. According to these results, women affected by metastatic breast cancer supplemented with 1.8 g of DHA during chemotherapy with antracyclins could increase their survival by 8 months.…”
Section: Breast Cancermentioning
confidence: 72%
“…Although adjustments in analysis attempt to isolate an independent effect, subtle differences or unmeasured variables cannot be completely examined in an observational study of this type. Laboratory and animal data have identified numerous mechanisms as to how marine fatty acids may inhibit carcinogenesis, including antiinflammatory, proapoptotic, antiproliferative, and antiangiogenic effects; downregulation of estrogen synthesis; and modulation of insulin sensitivity (1,(30)(31)(32). EPA and DHA are thought to reduce inflammation through the inhibition of NF-kB (33), which acts as a transcription factor for targets associated with inflammation, including IL-6 and cyclooxygenase-2 (34).…”
Section: Discussionmentioning
confidence: 99%
“…Although the general perception exists that diets enriched in n-3 relative to n-6 fatty acids have a broad range of healthrelated benefits, a review of the literature reveals that the epidemiologic data in support of an inverse relationship between n-3 fatty acid consumption and breast cancer risk are mixed (1)(2)(3)(4)(5)(6). Moreover, the preclinical data on the role of n-3 fatty acids in mammary carcinogenesis is similarly mixed (inhibition, no effect, or promotion of carcinogenesis), and the quality of the experiments varies so markedly that it is difficult to compare results across studies (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%